Psychopathological profile and readiness to change among drug addicts in Malaysia - Wan Sulaiman, Wan Shahrazad; Ab. Rahman, Roseliza Murni; Mohamad, Lukman @ Zawawi; Ahmad Zamani, Zainah; Jusoff, Kamaruzaman; Ibrahim, Fauziah; Zainal, Arifin (IDOSI Publications, 2011)
The severity of psychopathological symptoms may influence the motivation to change drug dependence behavior. Therefore, this study was conducted to examine the predictive relationship between psychopathological symptoms and readiness to change among drug addicts in Malaysia. The study employed survey research involving the administration of the Symptoms Checklist-90-Revised (SCL-90-R) and the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES). A total of 599 respondents in six rehabilitation centers in Malaysia participated in this study. Results showed that there were significant correlations between several psychopathological symptoms with recognition, ambivalence and taking steps. Findings also showed that psychopathological symptoms did not predict Recognition, interpersonal-sensitivity and paranoia predicted significantly Ambivalence, while only symptom of hostility predicted significantly Taking Steps. This demonstrated that high level of psychopathology among drug addicts undergoing treatment may compromise their motivation to change. Those who did not recognize that they have problems with addiction were ambivalent about changing and were unwilling to take steps to change their addictive behavior.